The short-term effect of gloving in combination with Traditional Thai Massage, heat, and stretching exercise to improve hand mobility in scleroderma patients - Kunavut Vannajak; Yodchai Boonprakob; Wichai Eungpinichpong; Supunnee Ungpansattawong; Ratanavadee Nanagara (Journal of Ayurveda and Integrative Medicine, 2014)
Background: Systemic sclerosis (SSc) is a chronic, multisystem connective tissue disorder characterized by autoimmune activation, microvascular endothelium damage, and excessive collagen proliferation. The most affected hand presents claw hand deformity and microvascular disease. Deformed hands can cause functional disability and decrease the quality of life. A daily home program can improve mobility of scleroderma patients. Objective: We sought to determine the effect of a daily home exercise program on hand mobility among scleroderma patients. Materials and Methods: This was a randomized control trial. Twenty-eight participants were divided into two groups, both of which received the same daily home treatment: Group 1 with gloves (n = 14) and Group 2 without gloves (n = 14). The 2-week daily home program combined traditional Thai massage (TTM) with stretching exercises and heat. Hand mobility was assessed using hand mobility in scleroderma (HAMIS). The study was conducted in patients who were already on vasodilator drugs. Results: Both groups showed a significant improvement in hand mobility after 2 weeks of daily home exercise program (P < 0.05). Wearing the glove, however, resulted in better thumb mobility. Conclusions: A daily home exercise program improved hand mobility among patients with scleroderma and wearing gloves may improve thumb mobility.